2021
DOI: 10.1038/s41467-021-22665-4
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 reads heterochromatic H4K20me3 to reinforce LINE-1 DNA methylation

Abstract: DNA methylation and trimethylated histone H4 Lysine 20 (H4K20me3) constitute two important heterochromatin-enriched marks that frequently cooperate in silencing repetitive elements of the mammalian genome. However, it remains elusive how these two chromatin modifications crosstalk. Here, we report that DNA methyltransferase 1 (DNMT1) specifically ‘recognizes’ H4K20me3 via its first bromo-adjacent-homology domain (DNMT1BAH1). Engagement of DNMT1BAH1-H4K20me3 ensures heterochromatin targeting of DNMT1 and DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 82 publications
(95 reference statements)
1
64
0
Order By: Relevance
“…The activity of the HUSH complex in humans contributes to the repression of old families of L1P and L1M retrotransposons in the introns of active genes [111]. DNA methylation and histone methylation are interrelated, thus, recently it was found that DNMT1 recognizes heterochromatin markers H3K9me3 and H4K20me3, which profoundly impacts DNA methylation [252,253]. A low level of expression in the mammalian embryonic and adult brains is observed for PIWI family proteins.…”
Section: Features Of L1 Regulation During Human Embryonic Developmentmentioning
confidence: 99%
“…The activity of the HUSH complex in humans contributes to the repression of old families of L1P and L1M retrotransposons in the introns of active genes [111]. DNA methylation and histone methylation are interrelated, thus, recently it was found that DNMT1 recognizes heterochromatin markers H3K9me3 and H4K20me3, which profoundly impacts DNA methylation [252,253]. A low level of expression in the mammalian embryonic and adult brains is observed for PIWI family proteins.…”
Section: Features Of L1 Regulation During Human Embryonic Developmentmentioning
confidence: 99%
“…Interestingly, DSB repair alters DNA methylation patterns ( Sriraman et al, 2020 ), but little is known about the mechanisms allowing DNA methylation restoration. Furthermore, the DNA methyltransferase DNMT1 can read heterochromatin histone marks thus protecting cells against ionizing radiation ( Ren et al, 2020 , 2021 ). These findings suggest a potential role for DNA methylation in controlling DSB repair responses, which is still to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Repression at the epigenetic level is mostly accomplished by the addition of repressive histone marks, mainly trimethylation of lysine 9 of histone H3 (H3K9me3) (Bulut-Karslioglu et al, 2014;Liu et al, 2014;He et al, 2019), trimethylation of lysine 20 of histone H4 (H4K20me3) (Ren et al, 2021), and histone H1 on LINE-1 loci (Healton et al, 2020), and by DNA methylation (Hata and Sakaki, 1997;Muotri et al, 2010). This is mediated by several sequence-specific repressors that directly bind to TEs and recruit epigenetic modulators.…”
Section: Multiple Layers Of Line-1 Repressionmentioning
confidence: 99%
“…These repressive mechanisms include regulation at the epigenetic level by the binding of epigenetic modifiers to the LINE-1 sequence, at the transcriptional level by sequence-specific repressive transcription factors binding to the LINE-1 promoter in the 5′UTR (5′ untranslated region), at the post-transcriptional level by degradation mechanisms (splicing, RNA interference or RNAi, autophagy, and stress granules), at the translational level via RNA binding proteins, at the level of the nuclear import of the RNA, and at the integration level by several factors belonging to the DNA repair machinery ( Pizarro and Cristofari, 2016 ). Repression at the epigenetic level is mostly accomplished by the addition of repressive histone marks, mainly trimethylation of lysine 9 of histone H3 (H3K9me3) ( Bulut-Karslioglu et al, 2014 ; Liu et al, 2014 ; He et al, 2019 ), trimethylation of lysine 20 of histone H4 (H4K20me3) ( Ren et al, 2021 ), and histone H1 on LINE-1 loci ( Healton et al, 2020 ), and by DNA methylation ( Hata and Sakaki, 1997 ; Muotri et al, 2010 ). This is mediated by several sequence-specific repressors that directly bind to TEs and recruit epigenetic modulators.…”
Section: Multiple Layers Of Line-1 Repressionmentioning
confidence: 99%